2014
DOI: 10.1364/boe.5.001664
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid FMT-MRI applied to in vivo atherosclerosis imaging

Abstract: Combining Fluorescent Molecular Tomography (FMT) with anatomical imaging, e.g. MRI facilitates interpreting functional information. Furthermore, using a heterogeneous model for light propagation has been shown in simulations to be superior to homogeneous modeling to quantify fluorescence. Here, we present a combined FMT-MRI system and apply it to heart and aorta molecular imaging, a challenging area due to strong tissue heterogeneity and the presence of air-voids due to lungs. First investigating performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The former normally requires a support from the anatomical imaging modalities with high soft tissue contrast, such as MRI or phase-contrast X-ray CT [8,46], and also can be potentially obtained by registry between the conventional micro-CT images and a standard digital mouse atlas. In both the methods some errors are inevitably introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former normally requires a support from the anatomical imaging modalities with high soft tissue contrast, such as MRI or phase-contrast X-ray CT [8,46], and also can be potentially obtained by registry between the conventional micro-CT images and a standard digital mouse atlas. In both the methods some errors are inevitably introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Abascal et al demonstrated that the normalized Born approximation approach tolerates uncertainty in the absorption heterogeneity to some extent, but fails to compensate for the effect of the unknown scattering heterogeneity in the model [6,7]. Another strategy is to fuse the structural information from anatomical imaging modalities such as X-ray CT and MRI to the modeling process [8][9][10], and to assign the experimentally measured or literaturepublished optical properties to different tissue regions [11]. This approach, despite considerably improving the images, usually leads to noticeable quantification errors because of the individual variations.…”
Section: Introductionmentioning
confidence: 99%
“…Detection fibers collect the emitted photons and direct them onto CCD camera. FMT can be combined with high-resolution imaging techniques such as CT or MR in order to refine anatomical features [ 46 , 47 ]. Besides cathepsin B [ 48 ], FMT is able to visualize MMP activity [ 49 ] as well as fluorescence autoantibodies [ 13 ••].…”
Section: Nirf Imaging Of Atherosclerosismentioning
confidence: 99%
“…FMT offers an improved penetration depth of light in the near-infrared spectrum and limited autofluorescence but has limited spatial resolution and is currently restricted to preclinical field or ex vivo human samples [ 256 ]. Moreover, multimodality imaging with the association of FMT-CT or -MRI holds promise for noninvasive imaging of murine models of atherosclerosis, adding anatomical details to molecular signals [ 257 , 258 , 259 ]. Macrophage content correlates with plaque vulnerability because the fibrotic cap can be destabilized by the secretion of matrix-degrading enzymes, contributing to acute thrombotic complications.…”
Section: Murine Models Of Atherosclerosis and Molecular Imaging Tamentioning
confidence: 99%